Development of the Human Potential of Ukraine in the Context of the Polish Experience - Tomchuk, O. (Економічний вісник Донбасу, 2019)
The factors of influence on quality of human potential are investigated in the article and regularities of potential development are revealed. The study found that the concept of sustainable development is embedded in the model of development of the EU and Ukraine, and emphasizes that ecological growth and development of human potential are complementary factors. The dynamics of macroeconomic indicators of Ukraine and Poland is analyzed. The quality of human potential is found to be correlated with: GDP per capita, real wages, unemployment, imports of goods and services and investments. The results of the study concluded that the analyzed factors in the majority have a negative impact on the quality of human potential of Ukraine. Prospects for further research are justification for modeling the quality of human potential. У статті досліджено фактори впливу на якість людського потенціалу та виявлені закономірності розвитку потенціалу. У результаті дослідження було виявлено, що концепція сталого розвитку, покладена в основу моделі розвитку і ЄС, і України, наголошує, що економічне зростання та розвиток людського потенціалу є взаємодоповнюваними факторами. Проаналізовано динаміку макроекономічних показників України та Польщі. Встановлено, що якість людського потенціалу знаходиться у взаємозв’язку з: ВВП на душу населення, реальною зарплатою, безробіттям, імпортом товарів та послуг та інвестиціями. За результатами дослідження дійшли до висновків, що проаналізовані чинники в більшості здійснюють негативний вплив на якість людського потенціалу України. Перспективою подальших досліджень є обґрунтування моделювання якості людського потенціалу. В статье исследованы факторы влияния на качество человеческого потенциала и выявлены закономерности развития потенциала. В результате исследования было выявлено, что концепция устойчивого развития, положенная в основу модели развития ЕС и Украины, отмечает, что экономический рост и развитие человеческого потенциала являются взаимодополняемыми факторами. Проанализирована динамика макроэкономических показателей Украины и Польши. Определено, что качество человеческого потенциала находится во взаимосвязи с: ВВП на душу населения, реальной зарплатой, безработицей, импортом товаров и услуг и инвестициями. По результатам исследования пришли к выводу, что проанализированные факторы в большинстве оказывают негативное влияние на качество человеческого потенциала Украины. Перспективой дальнейших исследований является обоснование моделирования качества человеческого потенциала.